Disaster knowledge factors in managing disasters successfully - Seneviratne, Krisanthi; Baldry, David; Pathirage, Chaminda (International Journal of Strategic Property Management, 2010)
The number of reported natural disasters has increased steadily over the past century and risen very sharply during the past decade. These bring about the loss of lives, property, employment and damage to the physical infrastructure and the environment. Disaster management efforts aim to reduce or avoid the potential losses from hazards, assure prompt and appropriate assistance to victims of disaster, and achieve rapid and effective recovery. While knowledge management can enhance the process of disaster management, there is a perceived gap in information coordination and sharing within the context of disaster management. Identifying key success factors will be an enabler to manage the disasters successfully. In this context, this study aims to identify and map key knowledge success factors for managing disasters successfully through capturing the good practices and lessons learned. The objective of this paper is to present the literature findings on factors which support successful disaster management. Accordingly the identified factors were classified into eight main categories as technological, social, legal, environmental, economic, functional, institutional and political.First Published Online: 10 Feb 2011